Research and Practice of Surveying and Mapping for Failed Large Modulus Cylindrical Gear - Ben Daochun (Jixie chuandong)
From tooth profile wear and the demand of match manufacturing,a set of field mapping method is proposed,which does not depend drawings,while by virtue of toothed parameter with accumulated manufacturing experience that included addendum circle,tooth root circle,helix angle,variable coefficient measuring,modulus and pressure angle determining. At the same time,two examples of the successful application for measuring are cited. It concludes that modulus of wear gear can be accurately calculated based on the mean value of length difference for cross- tooth normal line,pressure angle can be determined based on the theory of alveolar bottom size,and the addendum helix angle can be estimated by the auxiliary template,thus the helix angle of helical gear is deduced. According to tooth root diameter,modulus,tooth number and helix angle,the modification coefficient is calculated finally. The mapping method can be used to guide the repair and pairing manufacture.